2019
DOI: 10.1556/019.70.2019.07
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition and antibacterial activity ofPteridium aquilinum(L.) Kuhn

Abstract: Introduction:The present work aims to study the chemical composition of Pteridium aquilinum (L.) Kuhn essential oil and its antibacterial activity against three important phytopathogenic Gram-negative bacteria: Erwinia amylovora, Pectobacterium carotovorum subsp. carotovorum, and Pseudomonas savastanoi pv. savastanoi. Methods: The chemical composition of P. aquilinum L. essential oil produced by hydrodistillation was determined by gas chromatography-mass spectrometry. The antibacterial activity was tested usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…phaseolicola and P. carotovorum pv. carotovorum (Horvath et al, 2010;Elshafie et al, 2016;Cadena et al, 2018;Bouchekouk et al, 2019;Della Pepa et al 2019;Elshafie et al, 2019;Elshafie et al, 2020;Camele et al, 2021), to the best of our knowledge there is no record available on the antibacterial activities of essential oils of H. italicum, I. graveolens, C. creticus, E. purpurea and H. perforatum against plant pathogenic bacterial disease agents used in this study.…”
Section: Resultsmentioning
confidence: 92%
“…phaseolicola and P. carotovorum pv. carotovorum (Horvath et al, 2010;Elshafie et al, 2016;Cadena et al, 2018;Bouchekouk et al, 2019;Della Pepa et al 2019;Elshafie et al, 2019;Elshafie et al, 2020;Camele et al, 2021), to the best of our knowledge there is no record available on the antibacterial activities of essential oils of H. italicum, I. graveolens, C. creticus, E. purpurea and H. perforatum against plant pathogenic bacterial disease agents used in this study.…”
Section: Resultsmentioning
confidence: 92%
“…The study highlights the possibility of utilizing natural resources, such as weed species, as a source of bioactive compounds. Similarly, in a study by Bouchekouk et al [112], the EO obtained from Pteridium aquilinum (bracken fern) demonstrated high potency against three economically important phytopathogenic bacteria. This EO was characterized by a high concentration of the compound linalool.…”
Section: Plant Species Other Than Lamiaceaementioning
confidence: 77%
“…carotovorum and P. savastanoi pv. savastanoi (Bouchekouk et al, 2019). Furthermore, essential oils from Verbena officinalis, Majorana hortensis and Salvia officinalis plants were found to inhibit the growth of Gram positive and Gram negative plant pathogenic bacterial disease agents Clavibacter michiganensis, Xanthomonas campestris, Pseudomonas savastanoi and P. syringae pv.…”
Section: Resultsmentioning
confidence: 99%